Oxford new syllabus primary Mathematics workbook 5B - Yee, Dr foong pui (Karachi : Oxford university press, 2019)
The Oxford New Syllabus Primary Mathematics Workbook 5B is a continuation of Workbook 5A and is designed for primary school students, typically in their fifth year. It serves as a companion workbook to Oxford New Syllabus Primary Mathematics Book 5 and provides additional exercises and activities to reinforce and deepen students' understanding of the advanced mathematical concepts introduced in the textbook.
Keywords: Mathematics : Textbook